PEMBENTUKAN LEMBAGA PEMASYARAKATAN KHUSUS TINDAK PIDANA PERPAJAKAN DALAM SISTEM HUKUM NASIONAL - Junial Subarkah; Junial Subarkah (Legalita, 2026)
Indonesia's correctional system, since its establishment in 1964, was designed as a rehabilitative institution prioritizing social reintegration. Nevertheless, the disparate treatment of tax crime convicts within general correctional facilities gives rise to substantial juridical concerns. Tax crimes possess sui generis characteristics that fundamentally distinguish them from conventional offenses, namely the massive dimension of state financial losses, the complexity of modus operandi, and significant asset recovery potential when correctional mechanisms are purposefully designed. This study aims to construct normative and comparative arguments for the establishment of a Special Correctional Institution for Tax Crimes (LPKTP) within the national legal system framework. The normative legal research method is employed, utilizing statutory, conceptual, and comparative approaches. Findings indicate that the constitutional foundation, legislative framework, and urgency of penal reform collectively support the establishment of such an institution, which structurally must integrate fiscal compliance development, state loss recovery, and competency-based social reintegration functions.